AKLIMATISASI BIBIT TANAMAN BUAH NAGA (Hylocereus undatus) PADA TINGKAT NAUNGAN BERBEDA - Basri, Hasan; Basri, Zainuddin; Syakur, Abd (AGROTEKBIS, 2013)
This study aims to determine the effect of shade level on the growth of plantlets dragon fruit . This study used a completely randomized design (CRD), which consists of three treatment that is shaded by 1 (N1), 2 (N2) and 3 (N3) waring layer. Each treatment was repeated three times so there are 9 units of the experiment. Each experimental unit consisted of 10 plants.Â Therfore, there are a total of 90 samples of plants were observed. The results showed that the 2, 4, 6 and 8 week after planting, waring with two layers of shade treatment (N2) shown a good value for all the observations such as number of shoots, plant height and stem diameter compared to waringwith one layer of shade (N1) and 3 layer (N3).